Petrografia, mineraloquímica e geoquímica do Stock Itabi, Domínio Macururé, sistema orogênico sergipano - Moreira, Rodolfo Cabelê (2023)
Stock Itabi has an area of 8 km² and is intrusive in the metasedimentary rocks of the Macururé Domain (metapelites and metarhythmites). The rocks of this body are massive, grayish and have an inequigranular phanerite texture. Enclaves of 1 to 25 cm with fine grain and angular shapes sometimes occur throughout the stock. Plagioclase, alkali feldspar, quartz and biotite make up the main mineralogy of the rocks. Epidote, titanite, apatite, opaque minerals and zircon also occur as accessory phases. Stock Itabi is essentially composed of two types of rocks (granodiorite and quartz-monzonite). The plagioclase of quartz-monzonites and granodiorites exhibits a composition of albite, oligoclase and andesine, while granite exhibits a practically homogeneous albite phase. The composition of the plagioclase of the quartzmonzodioritic enclave varies from albite to oligoclase. The micas present in stock are Febiotite, phengite and muscovite. Biotite chemical data indicate that these crystals crystallized under temperatures of 636 – 811 °C and pressures between 1.8 and 3.7 kbar. In monzonites and granodiorites, the contents of SiO2, Al2O3, K2O, Na2O, CaO, Fe2O3, TiO2, MgO, P2O5 and MnO are between 61-65%, 15.4-16.2%, 3.3- 4.1%, 3.6-4.0%, 2.5-4.7%, 4.2-5.8%, 0.37- 0.64%, 1.79-2.5%, 0.24-0.33% and 0.06-0.08%, respectively. The rocks of Stock Itabi are similar to magnesian granites, are metaluminous to peraluminous, and have a shoshonite signature.